FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN DUKUNGAN KELUARGA TENTANG ASI EKSKLUSIF DENGAN PERTUMBUHAN BAYI UMUR 6 BULAN DI WILAYAH KERJA PUSKESMAS SUKARAMAI MEDAN TAHUN 2020 - HELENA FRANSYSCA (LP2MTBM MAKARIOZ, 2020)
This research aims to find out the relationship of maternal knowledge and attitude as well as family support about exclusivebreast milk with the growth of 6-month-old babies in the working area of Sukaramai Medan health center. This type ofresearch is analytically descriptive with cross sectional studies with a population of 32 samples. The sampling techniqueused is total sampling as well as using a hypothesis with a chi-square test. There is a significant relationship of maternalknowledge with the growth of a 6-month-old baby, obtained X2atung greater than X2tabel (12,264> 9,488). There is asignificant relationship of maternal attitude with the growth of a 6-month-old baby, obtained X2tatung greater than X2tabel(15,596> 9,488). There is a significant relationship between family support and the growth of 6-month-old babies, obtainedby X2000 (29,112> 9,488). Conclusion there is a significant relationship of maternal knowledge and attitude as well as familysupport with the growth of 6-month-old babies in the working area of Sukaramai Medan health center.